PENGEMUDI KENDARAAN BERMOTOR YANG MELANGGAR HUKUM YANG MENIMBULKAN KERUGIAN DAN KECELAKAAN LALU LINTAS YANG DI ATUR DALAM PASAL 1365 KUH PERDATA - Rizky Purnomo Aji; Mas Agus Priyambodo (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
Road traffic problems that arise today, especially traffic violations and incidents of traffic accidents, tend to continue to increase which in turn will cause anxiety for road users. Drivers' unlawful acts cause many losses to other parties, so it is only natural that the injured party demands the driver's responsibility to compensate for the loss. This will not cause many problems if the driver is also the owner of his own motorized vehicle. However, in general, drivers of public vehicles such as public transport buses, only have the status of tenants or workers who are in a financial situation unable to pay compensation. So it is not uncommon for the fulfillment of their responsibility to pay compensation not to be commensurate with the losses that have been caused. A driver who commits an unlawful act causing a traffic accident which results in a loss to the victim must compensate for the loss that has committed an unlawful act and causes a loss, then he is obliged to compensate for that loss.